Faktor-Faktor yang Mempengaruhi Kepuasan Kerja dan Implikasinya terhadap Kinerja Karyawan Kebun Kelapa Sawit PT Langkat Nusantara Kepong - Zulham, Zulham; Lubis, Yusniar; Lubis, Syaifuddin (Universitas Medan Area, 2020)
This study aims to determine and analyze the influence of organizational culture, work climate, and welfare facilities on job satisfaction and its implications for employee performance in PT. Langkat Nusantara Kepong. This research method uses a quantitative approach, the type of research is a survey. The sample was determined by a random sampling method of 226 people. Data collection through questionnaires. Data were analyzed using path analysis. The results showed that partially, organizational culture, work climate and welfare facilities had a positive and significant effect on employee job satisfaction. The highest influence value is the variable of organizational culture, meaning that organizational culture has a more dominant influence on employee job satisfaction, with a total effect of 36.40% (direct effect of 31.03%). Simultaneously, organizational culture, work climate and welfare facilities directly and indirectly have a positive and significant effect on employee job satisfaction. Employee job satisfaction is an intervening variable of organizational culture, work climate and welfare facilities to employee performance, because there is an increase in the influence of organizational culture, work climate and welfare facilities on employee performance by 16.12% if through job satisfaction variables.